AMP-activated protein kinase (AMPK) activator drugs reduce mechanical allodynia in a mouse model of low back pain. Issue 11 (20th September 2019) - Das, Vaskar; Kroin, Jeffrey S; Moric, Mario; McCarthy, Robert J; Buvanendran, Asokumar
Abstract : Background and objectives: Intervertebral disc herniation is one of the common causes of low back pain. Adenosine monophosphate (AMP)-activated protein kinase (AMPK) activator drugs have been shown to reduce pain in several animal models. The present study examines if early treatment with the drug metformin, an indirect AMPK activator, and/or O304, a new direct AMPK activator, can reduce the mechanical hypersensitivity that develops after lumbar disc puncture in mice. Methods: The L4/L5 and L5/L6 discs in male and female mice were exposed via a retroperitoneal approach and a single puncture was made at the midline of each disc. Mice were randomized into four drug treatment groups: (1) vehicle; (2) metformin 200 mg/kg; (3) O304 200 mg/kg; (4) metformin 100 mg/kg plus O304 100 mg/kg; plus one untreated sham surgery group. Drugs were administered by oral gavage starting 7 days after disc puncture and repeated for six more days. Mechanical allodynia in the plantar hindpaw was measured presurgery and up to day 28. Results: 7 days after disc puncture, female mice had lower von Frey thresholds than male mice, difference −0.46 g, 95% CI −0.34 to −0.60, p<0.001. Gender adjusted von Frey area under the curve's (AUC's) between days 7 and 28 for metformin and/or O304 were greater (reduced allodynia) compared with vehicle-treated mice. The difference of mean AUC's was: metformin, 41.1 g*d, 95% CI of the difference 26.4 to 54.5, O304, 44.7 g*d, 95% CI of the difference 31.0 to 57.4, drug combination: 33.4 g*d; 95% CI of the difference 18.1 to 46.9. No gender by treatment interactions were observed. Conclusions: Lumbar disc puncture in mice produces consistent mechanical hypersensitivity, and postinjury treatment with AMPK activator drugs (indirect and direct) reduces the mechanical hypersensitivity.